A centrin–Sfi1 myoneme fishnet powers ultrafast calcium-triggered contraction in the giant ciliate Spirostomum ambiguum - Joseph Lannan; Carlos Floyd; L. X. Xu; Peter M. Thompson; Connie Yan; Wallace F. Marshall; Suriyanarayanan Vaikuntanathan; Aaron R. Dinner; Jerry E. Honts; Saad Bhamla; Mary Williard Elting (Proceedings of the National Academy of Sciences, 2026)
Spirostomum is a giant unicellular ciliate that contracts to a quarter of its body length in less than five milliseconds, achieving an order of magnitude higher fractional shortening rate than actomyosin-based systems. This ultrafast contraction is powered by myonemes, calcium-activated protein networks at the cortex whose biochemical mechanism remains unclear. We quantify changes in cortical microtubules, membrane ruffles, and the fishnet-like myoneme mesh during contraction, and develop multiscale models that connect local myoneme shortening to whole-cell shape change. Centrin and an Sfi1 homolog colocalize with the myoneme by immunofluorescence and localize to the myoneme by immunogold electron microscopy. Coarse-grained mesh simulations reproduce the measured deformations and show that fishnet geometry, together with volume conservation, leads to uniform contraction. Finally, we reconstitute a Spirostomum centrin–Sfi1 repeat complex in vitro and measure calcium-dependent compaction and self-association, supporting a molecular basis for myoneme contractility. Together, these results underpin a multiscale model in which calcium-responsive centrin–Sfi1 structures are the central contractile element in Spirostomum and suggest design principles for fast, calcium-triggered, chemomechanical contractile networks that operate without actomyosin or ATP.